Congoville Contemporary Artists Tracing Colonial Tracks. Hedendaagse kunstenaars bewandelen koloniale sporen - Boons, Pieter; Colard, Sandrine (Leuven University Press, 2021)
Companion to the exhibition CONGOVILLE, Middelheim Museum, May 2021 - October 2021One hundred years after the founding of the École Coloniale Supérieure in Antwerp, the adjacent Middelheim Museum invites Sandrine Colard, researcher and curator, to conceive an exhibition that probes silenced histories of colonialism in a site-specific way. For Colard, the term Congoville encompasses the tangible and intangible urban traces of the colony, not on the African continent but in 21st-century Belgium: a school building, a park, imperial myths, and citizens of African descent. In the exhibition and this adjoining publication, the concept Congoville is the starting point for 15 contemporary artists to address colonial history and ponder its aftereffects as black flâneurs walking through a postcolonial city.Due to the multitude of perspectives and voices, this book is both a catalogue and a reference work comprised of artistic and academic contributions. Together, the participating artists and invited authors unfold the blueprint of Congoville, an imaginary city that still subconsciously affects us, but also encourages us to envision a decolonial utopia.Een eeuw na de oprichting van de École Coloniale Supérieure in Antwerpen nodigt het naburige Middelheimmuseum onderzoeker en curator Sandrine Colard uit om een tentoonstelling te creëren die sitespecifiek peilt naar de stille geschiedenissen van het kolonialisme. Congoville duidt op de zichtbare en onzichtbare stedelijke sporen van de kolonie, niet op het Afrikaanse continent, maar pal in het België van vandaag: een schoolgebouw, een park, imperialistische mythes en burgers van Afrikaanse origine. Doorheen de tentoonstelling en deze bijhorende publicatie is Congoville de context waarbinnen 15 hedendaagse kunstenaars, als zwarte flâneurs op pad in een postkoloniale stad, het koloniale verleden en de impact ervan adresseren.Door de veelheid aan perspectieven en stemmen is dit boek tegelijk een catalogus en een naslagwerk met zowel academische als artistieke bijdragen. Samen ontvouwen de betrokken kunstenaars en auteurs de blauwdruk van Congoville, een imaginaire stad die ons nog steeds onbewust in haar greep houdt, maar ons ook aanspoort om na te denken over een de-koloniaal utopia.With contributions by/Met bijdragen van: Pieter Boons, Sandrine Colard, Filip De Boeck, Bas De Roo, Nadia Yala Kisukidi, Sorana Munsya & Léonard Pongo, Herman Van Goethem, Sara Weyns, Nabilla Ait DaoudParticipating artists/Deelnemende kunstenaars: Sammy Baloji, Bodys Isek Kingelez, Maurice Mbikayi, Jean Katambayi, KinAct Collective, Simone Leigh, Hank Willis Thomas, Zahia Rahmani, Ibrahim Mahama, Ângela Ferreira, Kapwani Kiwanga, Sven Augustijnen, Pascale Marthine Tayou, Elisabetta Benassi, Pélagie Gbaguidi